Analysis of the Determination of Factors Influencing Foreign Direct Investment in ASEAN for the Period 2019-2023 - Rista Fauziyah Yuliani; Syofriza Syofyan; Ida Busnetty (International Journal of Economics Accounting and Management, 2025)
This study aims to analyze the determinants of Foreign Direct Investment in ASEAN during the 2019–2023 period, considering economic and institutional factors. The main issue raised is the fluctuation of FDI inflows in ASEAN countries which are not always in line with economic growth, political stability, and the quality of regulations of each country. To answer this problem, a quantitative approach is used with a panel data regression model. The independent variables explained include Gross Domestic Product, Labor Force Participation Rate, Wages, Political Stability, Regulatory Quality, Inflation, and Interest Rates. The results of the analysis show that GDP has a significant positive effect on Foreign Direct Investment, Wages show a significant negative effect on Foreign Direct Investment, Labor Force Participation Rate and Interest Rates show a positive sign but do not significantly influence Foreign Direct Investment. While inflation has a negative sign but does not significantly influence Foreign Direct Investment. The Stability and Regulatory Quality variables show a negative sign that is not significant on foreign direct investment. This study concludes that the combination of economic growth and institutional strengthening is the main key in attracting Foreign Direct Investment. Therefore, for ASEAN countries that want to increase the attractiveness of foreign investment, it is necessary to focus not only on economic growth, but also on institutional reforms that support a long-term investment climate.